2022
DOI: 10.3354/ab00755
|View full text |Cite
|
Sign up to set email alerts
|

Ground-truthing daily and lunar patterns of coral reef fish call rates on a US Virgin Island reef

Abstract: Coral reefs comprise some of the most biodiverse habitats on the planet. These ecosystems face a range of stressors, making quantifying community assemblages and potential changes vital to effective management. To understand short- and long-term changes in biodiversity and detect early warning signals of decline, new methods for quantifying biodiversity at scale are necessary. Acoustic monitoring techniques have proven useful in observing species activities and biodiversity on coral reefs through aggregate app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Yet in other studies, low frequency SPL alone had little relationship with reef composition (Lamont et al, 2022b;Williams et al, 2022) or had partial or mixed success (Bertucci et al, 2016;Dimoff et al, 2021). Additionally, while fish call rates have revealed similar trends to low frequency SPL at a single site, Ferguson et al (2022) showed that the direct relationship between these two variables was not significant. Fewer studies have examined the daily fluctuations in SPL, despite documented increases in fish sound production around dawn and dusk (Winn et al, 1964;Parmentier et al, 2010).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Yet in other studies, low frequency SPL alone had little relationship with reef composition (Lamont et al, 2022b;Williams et al, 2022) or had partial or mixed success (Bertucci et al, 2016;Dimoff et al, 2021). Additionally, while fish call rates have revealed similar trends to low frequency SPL at a single site, Ferguson et al (2022) showed that the direct relationship between these two variables was not significant. Fewer studies have examined the daily fluctuations in SPL, despite documented increases in fish sound production around dawn and dusk (Winn et al, 1964;Parmentier et al, 2010).…”
Section: Introductionmentioning
confidence: 74%
“…Summaries of the reef community assessments are briefly described below but can be found in more detail in earlier work (Kaplan et al, 2015;Dinh et al, 2018;Formel et al [in preparation]). Tektite Reef (18.30962 N, 64.72218 W) is considered an acoustically rich reef, correlating with high fish diversity and coral cover (Kaplan et al, 2015;Ferguson et al, 2022; Table 1). Yawzi Point (18.31458 N, 64.72609 W) was selected as an intermediate quality reef and is characterized by slightly lower fish abundances and diversity (Friedlander and Beets, 2008) and generally lower hard coral cover (Edmunds, 2013; Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acoustic monitoring is a reliable and noninvasive method of observing coral reef ecosystems, with increased noise from fish and invertebrates associated with healthier reefs [2,[4][5][6]. A single acoustic sensor in a reef may record hundreds of fish sounds and thousands of invertebrate sounds per minute, providing an aggregated measurement of biological activity which may allow for the early detection of changes in population abundance and behavior [7,8]. Coral reef soundscapes also act as a beacon for recruiting pelagic fish and crustacean larva [9][10][11], and recent restoration efforts have been aided by artificial playback of healthy reef sounds to promote recruitment [12].…”
Section: Introductionmentioning
confidence: 99%